2008
DOI: 10.1152/japplphysiol.01016.2007
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin synthesis can be inhibited locally by infusion of NSAIDS through microdialysis catheters in human skeletal muscle

Abstract: Mikkelsen UR, Helmark IC, Kjaer M, Langberg H. Prostaglandin synthesis can be inhibited locally by infusion of NSAIDS through microdialysis catheters in human skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…However, the intramuscular levels reported in that study are similar to those reported in middle-aged and younger individuals (29,49,50). In addition, low-level muscular work does not increase PGE 2 levels (30, 50), whereas resistance and aerobic exercise stimulate the muscle to produce PGE 2 and/or PGF 2␣ during and/or after exercise (15,49,50,67,123,126). Furthermore, increasing the workload during aerobic exercise increases the muscle production of PGE 2 (15,49).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…However, the intramuscular levels reported in that study are similar to those reported in middle-aged and younger individuals (29,49,50). In addition, low-level muscular work does not increase PGE 2 levels (30, 50), whereas resistance and aerobic exercise stimulate the muscle to produce PGE 2 and/or PGF 2␣ during and/or after exercise (15,49,50,67,123,126). Furthermore, increasing the workload during aerobic exercise increases the muscle production of PGE 2 (15,49).…”
supporting
confidence: 75%
“…There are somewhat limited data on PG synthesis and muscle protein metabolism at rest or after exercise in response to oral consumption of over-the-counter COX inhibitors (82,126,128). Mikkelsen et al (67) have shown that an intramuscular infusion of a relatively low dose of the prescription COX inhibitor indomethacin reduced PGE 2 levels in the muscle during and after resistance exercise by ϳ85%. This same COX-inhibitor delivery approach during and for a few hours after resistance exercise did not influence muscle protein synthesis measured near the infusion site 24 h later (69).…”
mentioning
confidence: 99%
“…Mechanical stimulation of skeletal muscle cells promotes local membrane PL cleavage, free intracellular AA accumulation, PG synthesis/release, and cell growth (45,54,55). Consistently, inhibition of PG synthesis via NSAID administration in young healthy humans in vivo blunts adaptive myofiber protein synthesis (52,53) and satellite cell proliferation (22,27,28) responses to resistance exercise. In contrast, skeletal muscle wasting associated with chronic inflammatory conditions, including cancer cachexia (24,44,47), arthritis (10), and aging-associated sarcopenia (36,51), has been reported to be improved by systemic NSAID treatment.…”
mentioning
confidence: 84%
“…In studies where NSAID is consumed orally, PG release is blocked systemically at the whole body level. Inserting microdialysis catheters into the muscle allows the infusion of NSAID directly into the muscle to exert effects locally, which was confirmed by detection of reduced levels of PGE 2 in dialysate collected from catheters inserted at distances of 1 cm and 4 cm, respectively, away from the infusion catheter (46). It is not possible to compare the concentration of NSAID infused in this study directly with doses administered orally in other studies, but the PG levels appeared to be similar (47).…”
Section: Effects Of Nsaids On Satellite Cellsmentioning
confidence: 59%
“…In this study, no significant time ϫ drug interaction was detected, but the lack of increase in the NSAID group suggests that NSAID may exert a negative effect on the satellite cell response to exercise. This hypothesis was tested further, again in young healthy male volunteers, by a different approach, where NSAID was infused directly into the working muscle (46,47). In studies where NSAID is consumed orally, PG release is blocked systemically at the whole body level.…”
Section: Effects Of Nsaids On Satellite Cellsmentioning
confidence: 99%